Engineer's estimate reliability and statistical characteristics of bids. Issue 1 (31st December 2016) - Tehrani, Fariborz M.
Abstract: The objective of this report is to provide a methodology for examining bids and evaluating the performance of engineer's estimates in capturing the true cost of projects. This study reviews the cost development for transportation projects in addition to two sources of uncertainties in a cost estimate, including modeling errors and inherent variability. Sample projects are highway maintenance projects with a similar scope of the work, size, and schedule. Statistical analysis of engineering estimates and bids examines the adaptability of statistical models for sample projects. Further, the variation of engineering cost estimates from inception to implementation has been presented and discussed for selected projects. Moreover, the applicability of extreme values theory is assessed for available data. The results indicate that the performance of engineer's estimate is best evaluated based on trimmed average of bids, excluding discordant bids.